DESIGNING A THREE-WHEELED BIKE FOR ROUGH TERRAIN NAVIGATION (International Journal of Food and Nutritional Sciences, 2022)
This paper aims to Design and Fabricate a 3-wheeled Electric bike with doublesuspension for rough terrain as well as high-speed riding. An electric bicycle is a tool that isproduced from a combination of a bike as a means of transportation which is added with anelectric component as its driving force. An electric bicycle (e-bike) is a motorized bicycle withan integrated electric motor used to assist propulsion. Many kinds of e-bikes are availableworldwide, but they generally fall into two broad categories: bikes that assist the rider's pedalpowerandbikesthataddathrottle.E-bikesuserechargeablebatteriesandtypicallyaremotor-powered, high-powered varieties can often travel more than 60kmph. The basic principle of 3Wheel E-Bike is that the electromotive force of an D.C. motor receives electrical energy storedin a D.C. battery. Our e-bike is designed using a unique innovative 3-wheel design where thefront 2 wheels are connected in a separate frame and the bike handle and body rest on themechanismthroughauniquesuspensionjointlinkagesetting.OurE-bikecanattainamaxspeedofup to 80Kmph andmileageof up to 70km.